Efektivitas Pendidikan Kesehatan Tentang Bantuan Hidup Dasar Menggunakan Metode Peer Education Terhadap Peningkatan Pengetahuan Siswa - Muhammad Wirandi; Insana Maria; Taufik Hidayat; Martini Nur Sukmawaty (Institut Kesehatan Suaka Insan, 2026)
Equipping high school students with Basic Life Support (BLS) skills is crucial for managing out-of-hospital cardiac emergencies, yet the comparative effectiveness of peer education versus conventional leaflet-based instruction in Indonesia remains underexplored. This quasi-experimental pretest-posttest study involved 60 twelfth-grade students at Senior High School 3 Banjarbaru. Participants were equally divided into an intervention group receiving peer-supported BLS training (n=30) and a control group receiving leaflet-based education (n=30). Knowledge was assessed using a validated 15-item questionnaire. While both interventions significantly improved BLS knowledge (Wilcoxon Signed-Rank Test: intervention, p < 0.001; control, p = 0.003), the peer-supported group demonstrated a greater score increase (from 1.83 ± 0.38 to 3.00 ± 0.00) compared to the control group (from 1.93 ± 0.25 to 2.23 ± 0.43). Furthermore, post-test knowledge scores were significantly higher in the intervention group (Mann-Whitney U = 36.000, p = 0.030). In conclusion, peer-supported BLS training is significantly more effective than leaflet-based education. Integrating peer-led or hybrid approaches into school curricula is recommended to optimize students' emergency preparedness.